Pembrolizumab related Guillain barre syndrome, a rare presentation in a patient with a history of lupus and bladder cancer - Vikram Sangani; Mytri Pokal; Mamtha Balla; Ganesh Prasad Merugu; Sreedhar Adapa; Srikanth Naramala; Venu Madhav Konala (Greater Baltimore Medical Center, 2021)
Immune checkpoint inhibitor-related neurotoxicity causing Guillain Barre Syndrome is relatively uncommon. We discussed an 80-year-old patient with known systemic lupus erythematosus who presented with lower extremity weakness, areflexia and then progressed to respiratory muscle and upper extremity weakness after receiving immunotherapy with checkpoint inhibitors for metastatic bladder cancer. With the increasing use of immunotherapy for the management of cancer, awareness of neurological autoimmune side effects is essential. Immune checkpoint inhibitor-mediated GBS can be severe and fatal if not diagnosed promptly. The hospitalists, neurologists, and oncologists should be aware of neurotoxicity related to immune checkpoint inhibitor therapy requiring a multidisciplinary approach to patient care. Prompt initiation of immunosuppressive therapy is required for the management of immune checkpoint inhibitor-related neurotoxicity.